Legal Protection of Dentists After Removing Wisdom Teeth Causes Death of Patients in Ngawi East Java - Murtika, Yohanna; Hidayati, Hidayati; Mandala, Subianta (Jurnal Global Ilmiah, 2024)
The development of dentistry to serve patients to get comfort and elegant appearance. Wisdom tooth extraction caused death in patients who were talked about in the mass media. The purpose of this study is to provide protection to dentists for handling patients and are protected by a code of medical ethics so that health services can be fulfilled properly. The method used is normative juridical by more specifically reviewing the legal case of wisdom tooth extraction against patients who cause death, analyzing based on legal standards of applicable laws and regulations. Using primary, secondary and tertiary legal data and legal products related to this study. The results of the study explained that the authority of dentists to take action on patients' teeth is part of professional, tidying, reducing the risk of respiratory tract infections and gum disease. Based on article 6 of Law No. 29 of 2004 concerning Medical Practice, it is explained that the Indonesian Medical Council has the role of regulating, ratifying, determining, and coaching doctors and dentists who practice medicine, in order to improve the quality of medical services in accordance with the code of medical ethics and free from accusations of malpractice.